A new model system swims into focus: using the zebrafish to visualize intestinal lipid metabolism in vivo. (August 2009) - Carten, Juliana D; Farber, Steven A
Many fundamental questions remain regarding the cellular and molecular mechanisms of digestive lipid metabolism. One major impediment to answering important questions in the field has been the lack of a tractable and sufficiently complex model system. Until recently, most studies of lipid metabolism have been performed in vitro or in mice, yet each approach possesses certain limitations. The zebrafish ( Danio rerio ) offers an excellent model system in which to study lipid metabolism in vivo, owing to its small size, genetic tractability and optical clarity. Fluorescent lipid dyes and optical reporters of lipid-modifying enzymes are now being used in live zebrafish to generate visible readouts of digestive physiology. Here we review recent advances in visualizing intestinal lipid metabolism in live larval zebrafish.